On the Determination of the Enthalpy of Fusion of α‐Crystalline Isotactic Polypropylene Using Differential Scanning Calorimetry, X‐Ray Diffraction, and Fourier‐Transform Infrared Spectroscopy: An Old Story Revisited. Issue 9 (11th November 2019) - Lanyi, Franz J.; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W.
Abstract : The crystallinity determination of polymers using differential scanning calorimetry (DSC) is a standard procedure in industrial and university research. Its value strongly depends on the enthalpy of fusion, which cannot be determined directly using DSC, but must be calibrated using external methods such as X‐ray diffraction (XRD) or density measurements. In addition, the determination of the enthalpy or heat of fusion is not trivial and thus error‐prone; hence, values from 60 to 260 J g −1 are quoted for polypropylene in the literature. It is therefore of great relevance to devise a consistent method to determine the heat of fusion. To determine the heat of fusion for polypropylene, a sample set with a broad range of crystallinities is produced using cooling rates between 1 and ≈3500 K min −1 . The melting enthalpy of the samples is determined using DSC measurements. The determination of the melting enthalpy based on XRD measurements is discussed in detail, validated using Fourier‐transform infrared spectroscopy (FTIR), and compared with values quoted in the open literature. Although two different approaches are used to determine the enthalpy of fusion, a value of 170 ± 3 J g −1 is determined. Abstract : A strategy is presented to determine the enthalpy of fusion of isotactic α‐crystalline polypropylene by combining measurements via differential scanning calorimetry (DSC), X‐ray diffraction (XRD), and Fourier‐transform infrared spectroscopy (FTIR). A method to produce samples that cover the range of experimentally achievable crystallinities is shown. The enthalpy of fusion is determined to be 170 ± 3 J g −1 .